Implementasi Manajemen Risiko Pada Unit Usaha Bahan Bangunan Prespektif Ekonomi Syariah (Studi Pada Toko Bangunan Mandiri PP.Nurul Jadid) - Anisatul Kamila; Romzatul Widad (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
In the era of globalization, competition in the business world of a business unit, especially in the field of building materials business units, is getting tighter. Thus, with the progress of globalization, the need for housing is increasing. Therefore, to adapt to the development of globalization, building materials business units must prioritize fast service, comfort, and strategic locations as well as competitive prices. The building materials industry has special characteristics that are very vulnerable to various types of risks. Therefore, risk management is an important solution in anticipating and handling potential losses from these risks. This study aims to determine the application of risk management in building materials business units from a sharia economic perspective, especially at Toko Bangunan Mandiri Pondok Pesantren Nurul Jadid, identifying and analyzing risks and implementing mitigation strategies that are useful for increasing business stability without eliminating sharia principles. The method used in the study is a qualitative method using a case study approach, namely by direct interviews with shop owners. The results of the study indicate that the main risks faced by Toko Bangunan Mandiri are market risks such as very tight competition, changes in consumer demand, and economic conditions and consumer purchasing power as well as human resource risks. Thus, to reduce this risk, the building materials business unit conducts sales analysis and product analysis such as grouping Fast Moving and Slow Moving Goods, as well as analyzing the income/salary earned by employees and selecting qualified Human Resources.